(untitled) (Majalah Kedokteran Bandung, 2022)
Vitamin D receptors are widely expressed in brain tissue, including in the limbic system that plays a role in children’s mental and emotional development. This study aimed to analyze the relationship between 25-(OH)-D level and children’s mental-emotional development during their first 1000 days of life. A cross-sectional study was conducted on children aged â‰¤2 years old in Waled and Sukabumi regions using secondary data from previous cohort investigations entitled "The Role of Vitamin D in Efforts to Reduce Maternal and Infant mortality". The measurement of 25-(OH)-D concentration and assessment of the mental-emotional development were performed using the Ages and Stages Questionnaires: Social-Emotional (ASQ-SE) questionnaire. Other child and maternal characteristics, and several laboratory results, were also obtained. Statistical analyses were performed using the Spearman rank, Pearson correlation test, and multivariate linear regression analysis. A total of ninety-two children were included, and the median vitamin D level of the population was 20.17 ng/mL (IQR 4.43–49.97). The correlation analysis showed that no significant relationship between children’s mental-emotional scores and the parameters tested, including the concentration of 25-(OH)-D (correlation coefficient 0.08; p=0.446). There was no relationship between the vitamin D concentration and mental-emotional development. Based on these results, it is concluded that there is no correlation between 25-(OH)-D concentration and children’s mental-emotional development during the first 1000 days of life. However, further investigations are recommended to eliminate various confounding factors.